Understanding Pre-Service Teachers’ Perception in Applying Teaching Media: A TPACK-Based Study - Fauziah, Shiva; Kalisa, Pasca (Journal of English Language and Education, 2025)
This study explores how English pre-service teachers at Semarang State University develop and apply digital teaching media using the Technological Pedagogical and Content Knowledge (TPACK) framework. In today’s digital learning environment, teachers are expected not only to master subject content but also to skillfully combine it with suitable teaching methods and digital tools. Based on the findings, the participants showed strong ability in using digital platforms such as Canva, Quizizz, Wordwall, and Google Classroom. They integrated these tools with their lesson plans to make learning more interactive, engaging, and student-centered. Although they faced challenges such as limited teaching time, unstable internet access, and a lack of school facilities they managed to adapt by modifying their teaching strategies and media use. These results confirm what suggested: that effective technology use in education requires a deep understanding of how content, pedagogy, and technology work together. This study highlights the importance of preparing future teachers with real-world experiences and practical digital skills to meet the demands of modern classrooms.